Spirapril effects on heart remodeling in patients with mild to moderate arterial hypertension - M. M. Beraya; V. V. Petriy; V. I. Buvaltsev; N. G. Sergushkina; V. I. Makolkin (Российский кардиологический журнал)
In total, 62patients with mild to moderate arterial hypertension underwent echocardiography and Doppler cardiography. For 12 weeks, all participants received spirapril, 6 mg/d. Spirapril therapy was associated with reduced left ventricular hypertrophy and pathological heart remodeling type number.